Encoding Numbers When Numbers Rotate to the Left or Right Space: Evidence from the Spatial-Numerical Association of Response Codes (SNARC) Effect - Qiangqiang Wang; Binran Ma; Mengxia Li; Xiaolin Ye; Jianing Yang (Studia Psychologica)
Previous studies indicated that the SNARC effect can stably present in numerical cognition, however how the orientation influence the SNARC effect when Arabic numbers were rotated to left or right space remains unclear. The present study rotated Arabic numbers 45° to the left or right space and randomly and centrally presented those rotated numbers for participants systematically to investigate above question in orientation task (experiment 1), parity task (experiment 2), and magnitude task (experiment 3) respectively. The results found that 1) the SNARC effect was absent, but orientation spatial association effect was present in the orientation classification task. 2) the SNARC effect was only present in the orientation-response consistent condition, but absent in the orientation-response inconsistent condition in the numerical parity task (experiment 2) and numerical magnitude classification task (experiment 3). From these results, it can be concluded that 1) rotating numbers to left or right can substantially influence the SNARC effect; 2) how rotated orientation influence the SNARC effect was moderated by the task performed when numbers were rotated to left or right space. These results imply that the additional cue can substantially influence the SNARC effect in processing of numbers and support the working memory account.